2023
DOI: 10.1111/jeb.14162
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and genealogical effects on DNA methylation in a widespread apomictic dandelion lineage

Abstract: DNA methylation in plant genomes occurs in different sequences and genomic contexts that have very different properties. DNA methylation that occurs in CG (mCG) sequence context shows transgenerational stability and high epimutation rate, and can thus provide genealogical information at short time scales. However, due to metastability and because mCG variants may arise due to other factors than epimutation, such as environmental stress exposure, it is not clear how well mCG captures genealogical information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Furthermore, while plant methylome responses to both biotic and abiotic stresses may be common, further studies suggest differences in how DNA methylation responds to stress both within and across plant species (Dubin et al, 2015;Galanti et al, 2022;Peña-Ponton et al, 2022). Conversely, methylation changes in CG context, and to a lesser extent CHG, are extremely stable and more often reflect genomic origin of an individual (Peña-Ponton et al, 2022;Ibañez et al, 2023). Opposing results have been reported in other plants species however ( (López et al, 2022;Van Antro et al, 2022).…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, while plant methylome responses to both biotic and abiotic stresses may be common, further studies suggest differences in how DNA methylation responds to stress both within and across plant species (Dubin et al, 2015;Galanti et al, 2022;Peña-Ponton et al, 2022). Conversely, methylation changes in CG context, and to a lesser extent CHG, are extremely stable and more often reflect genomic origin of an individual (Peña-Ponton et al, 2022;Ibañez et al, 2023). Opposing results have been reported in other plants species however ( (López et al, 2022;Van Antro et al, 2022).…”
Section: Introductionmentioning
confidence: 95%
“…In other words, populations or accessions which are genetically identical, could be distinguished by their distinct CG and CHG methylation patterns. This has already been observed in some plant species, where CG and CHG methylation patterns best explained the geographical origin of individuals rather than the treatments individuals were exposed to (Ibañez et al, 2023;Peña-Ponton et al, 2022). (Bossdorf et al, 2010;Cubas et al, 1999;Ehrenhofer-Murray, 2021;Entrambasaguas et al, 2021;Hansen et al, 2022;Herman & Sultan, 2011;Herrera & Bazaga, 2013;van Dooren et al, 2020).…”
Section: Transgenerational Inheritance Of Dna Methylation In All Plan...mentioning
confidence: 61%
“…In species such as A. thaliana, Populus nigra and Thlaspi arvense, CHH appears to be the most responsive cytosine context to a change in environment (Dubin et al, 2015;Galanti et al, 2022;Peña-Ponton et al, 2022). Conversely, methylation changes in CG context, and to a lesser extent CHG, are extremely stable and more often reflect genomic origin of an individual (Ibañez et al, 2023;Peña-Ponton et al, 2022). However, some studies have suggested that much of the variation in DNA methylation has limited to no functional relevance, regardless of context, as changes in methylome profiles may be but a by-product of genomic or transcriptomic changes (Bewick & Schmitz, 2017;Secco et al, 2015).…”
Section: Supplementary Data S31: Mean Coverage Distribution Of Indivi...mentioning
confidence: 99%
See 1 more Smart Citation